(untitled) (Interdisciplinary Studies Journal, 2023)
This article addresses the implications of remote teaching during the Covid-19 pandemic on the activities of teachers in a rural educational institution in the municipality of São Lourenço do Sul. The investigation took place throughout 2020 and 2021, a period during which remote classes and teleworking were implemented in the state education system in Rio Grande do Sul. This study sought to investigate the practices developed by teachers to reach students during this period, as well as the ways in which the pandemic affected their routines. It was found that, from a didactic standpoint, remote teaching led teachers to find different ways to reach students, considering that many students prioritized agricultural activities on their properties. Financially, it required financial investments for a portion of the interviewees and highlighted the undervaluation of education professionals.